Multicomponent ceramic materials on the basis of PZT for the production of piezoelectric resonators - D. Bochenek; Z. Surowiak; S. V. Gavrilyachenko; M. F. Kupriyanov (Archives of Acoustics)
Investigations on the influence of the PbTiO3 content on the crystalline and domain structure of PZT-based four-component solid solutions have been performed. It has been shown that there is a close relation between the structure and temperature stability of the resonance frequency (fr) of the fabricated piezoceramic transducers. Better and more stable results have been obtained by doping and modifying the basic chemical composition obtaining Pb(Zr1-xTix)O3. The compositions with minimal [ampersand]Delta;fr/fr, within the temperature range T=213-358K (in relation to room temperature Tr=293K), exhibited (i) the smallest internal friction (Qm-1), (ii) the highest mechanical quality (Qm), (iii) high values of spontaneous deformation of the elementary cell ([ampersand]delta;T and [ampersand]delta;Re), (iv) the complex a-c-domain structure in the tetragonal phase (T) and the simple domain structure in the rhombohedral phase (Re). The practical result of the present work was the fabrication of piezoceramic electric band filters exhibiting [ampersand]Delta;fr/fr[ampersand]lt; 0.2[ampersand]percent; and a high mechanical quality factor (Qm=3225).